Effect of moderately increased thyroid‐stimulating hormone levels and presence of thyroid antibodies on pregnancy among infertile women - So, Shuhei (Reprod Med Biol, 2019)
PURPOSE: To study the effects of mildly elevated thyroid‐stimulating hormone (TSH) levels and thyroid antibodies on pregnancy rates among infertile women and their potential contribution to prolonged infertility treatment. METHODS: This case‐control study included 1479 women who underwent infertility treatment between March 2015 and August 2017. Cumulative pregnancy and miscarriage rates after assisted reproductive technology (ART) or non‐ART treatments were compared between women with TSH <2.5 mIU/L and those with TSH 2.5‐3.5 mIU/L and between women with and without thyroid antibody positivity. RESULTS: The cumulative pregnancy rate of women with TSH 2.5‐3.5 mIU/L was similar to that of women with TSH <2.5 mIU/L in the non‐ART (hazard ratio [HR], 0.85; 95% confidence interval [CI], 0.56‐1.23) and ART (HR, 1.17; 95% CI, 0.93‐1.47) groups. Thyroglobulin antibody (TgAb) and thyroid peroxidase antibody (TPOAb) had no correlation with cumulative pregnancy rates. In the non‐ART and ART groups, HRs for TgAb were 0.87 (95% CI, 0.55‐1.32) and 1.09 (95% CI, 0.84‐1.39) and HRs for TPOAb were 0.88 (95% CI, 0.52‐1.39) and 1.29 (95% CI, 0.97‐1.68), respectively. CONCLUSIONS: Cumulative pregnancy rates and miscarriage rates were similar between women with TSH <2.5 mIU/L and those with TSH 2.5‐3.5 mIU/L and were independent of thyroid antibody positivity.